Homobimetallic Ferrocene derived from 1,4-phenylenebis(1H-1,2,3-triazole-4,1-diyl))diphenol as burning rate catalyst - Morales, Cesar; Valdebenito, Cristian; Abarca, Gabriel (Journal of the Chilean Chemical Society, 2025)
To comprehend the synergistic catalytic effect on the thermal decomposition of ammonium perchlorate (AP) when two ferrocene (Fc) fragments are in the same molecule linked by the ligand 4,4’-(1,4-phenylenebis(1H-1,2,3)-triazol-4,1-diyl))diphenol (1) was synthesized a bimetallic ferrocene compound (2), and compared with other homo- and monobimetallic ferrocene compounds already reported, as a potential burning rate catalyst. We conducted a differential scanning calorimetry (DSC) analysis of compound (2), which showed a decrease the high-temperature decomposition (HTD) of Ammonium Perchlorate (AP) to 379 ºC. Our results suggest that the ferrocene is a suitable and competitive alternative to be used as an enhancer of solid composite propellants.